2012
DOI: 10.1186/1749-8090-7-87
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation following cardiac surgery: risk analysis and long-term survival

Abstract: BackgroundWe studied potential risk factors for postoperative atrial fibrillation (POAF) in a large cohort of patients who underwent open-heart surgery, evaluating short- and long-term outcome, and we developed a risk-assessment model of POAF.MethodsA retrospective study of 744 patients without prior history of AF who underwent CABG (n = 513), OPCAB (n = 207), and/or AVR (n = 156) at Landspitali Hospital in 2002–2006. Logistic regression analysis was used to study risk factors for POAF, comparing patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
0
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 30 publications
6
121
0
24
Order By: Relevance
“…41 patients with postoperative AF also had longer total length of hospital stay, and specifically the stay in ICU can more than doubled. 42 Postoperative (<30 days) mortality was 5% in patients who were diagnosed with postoperative AF, when compared with only 0.7% in patients with postoperative normal sinus rhythm. The difference in survival is also reflected in long-term survival: an 83% 5-year survival for patients with postoperative AF and 93% for patients with postoperative normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 patients with postoperative AF also had longer total length of hospital stay, and specifically the stay in ICU can more than doubled. 42 Postoperative (<30 days) mortality was 5% in patients who were diagnosed with postoperative AF, when compared with only 0.7% in patients with postoperative normal sinus rhythm. The difference in survival is also reflected in long-term survival: an 83% 5-year survival for patients with postoperative AF and 93% for patients with postoperative normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in survival is also reflected in long-term survival: an 83% 5-year survival for patients with postoperative AF and 93% for patients with postoperative normal sinus rhythm. 42 Autonomic imbalance and the interaction between inflammatory substances inducing GP hyperactivity play a major role in the mechanism of postoperative AF. 43,44 The operative procedure results in release of inflammatory substances that could activate nerve endings of the atrial neural network, instigating AF, as shown in experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Nýtil-komið gáttatif er einnig algengasti minniháttar fylgikvilli eftir aðrar hjartaskurðaðgerðir hér á landi og erlendis, en þá er tíðnin á bilinu 30-50%. 20,21 Af alvarlegum fylgikvillum reyndust fylgikvillarnir hjartadrep í kringum aðgerð (15,2%) og enduraðgerð vegna blaeðingar algengastir. Tíðni enduraðgerða vegna blaeðingar var 14,3%, sem er haerra en í flestum erlendum rannsóknum þar sem hlutfallið er oftast á bilinu 2-10%.…”
Section: Umraeðaunclassified
“…1-3 POAF has a peak incidence on postoperative day 2 4 and is associated with several adverse outcomes, including increased cardiovascular, renal, and cerebral complications; increased cost of care and resource utilization; and decreased long-term survival. 1,[5][6][7][8] Hypomagnesemia has been associated with an increased risk of AF, both after cardiac surgery 9,10 and in ambulatory settings. 11,12 Hypomagnesemia is believed to promote AF through a variety of mechanisms, including effects on atrioventricular conduction, action potential duration, and the atrial effective refractory period.…”
Section: Introductionmentioning
confidence: 99%